A sustainable system of a traditional precision agriculture in a Maya homegarden: Soil quality aspects - Flores-Delgadillo, Lourdes; Fedick, Scott L.; Solleiro-Rebolledo, Elizabeth; Palacios-Mayorga, Sergio; Ortega-Larrocea, Pilar; Sedov, Sergey; Osuna-Ceja, Esteban (Soil & tillage research, 2011)
► The soil date corresponds to the Maya occupation peak. ► The values of the “ S” index indicated good physical soil quality. ► Fe oxides and organic materials influence the soil color and high soil aggregation. ► The cultivation systems include crop adaptation to thicker soil areas. ► The crop adaptation is known traditionally as “precision agriculture”. Homegardens or “ solares” have a long history of intensive cultivation by the Maya in southeastern Mexico and Central America, and have recently been the subject of increasing studies that characterize them as “multistrata agroforestry systems”, although no soil evaluation has been reported. We have conducted this study in a traditional homegarden named “El Naranjal”, a rural village in the north of Quintana Roo, Mexico, in order to evaluate soil date and quality from this specific site, being the soil the main factor of this traditional Maya agroforestry management system. The 14C analysis of the A 1 horizon humic fraction, from the deepest soil profile exposed in a karstic depression, gave a date that corresponds with the occupation of the site at the Maya peak of the mayan possession from the Late Preclassic to Early Classic transition, beginning about 100 B.C. The soils found (Rendzic Leptosols) into El Naranjal homegarden are well structured, very dark brown, shallow, and have an abrupt contact with the limestone bedrock at a highly variable depth. According to this fact, soil depth showed along the studied transect, the highest variation (variation coefficient = 72%) compared to Ranch Santa Maria (VC = 46.3%) and El Eden (43%) soils, being sites with similar heterogeneity degrees. The pH values ranged from neutral to moderately basic (7.10–8.00); this parameter that influences the humification and mineralization processes, showed a low VC (3.37%). Organic matter content varied from high to very high (7.30–20.23%, at 30–80 cm deep, and ranged in the deepest soil profiles from 2.00% to 3.98%). High levels of P retention (21.5–83.0%) were found; this characteristic is related to high values of exchangeable Ca 2+ and dithionite-extractable Fe, present in all studied profiles. The soils are clayish and have middle to high values of hydraulic conductivity (4.8–64.8 cm h −1) that displayed a high VC (65.74%). The values of the “ S” index (soil physical quality index) fluctuated between 0.059 and 0.068, indicating good physical soil quality, with regard to the proposed critical value of 0.035. According to other physical and chemical properties, it was found that the soils from this homegarden have favorable qualities for air transport, heat, water and soluble substances. The iron oxides and organic components are responsible for soil color, high aggregation with good stability and consequently of their high porosity. But, on the other hand, the highly variable soil depth (often insufficient for the development of root systems) and the large level of P retention (phosphorus-fixing capacity) are the most obvious physical and chemical disadvantages to crop growth. These are also the most common and restrictive factors in many soils from the Yucatán Peninsula. However, results showed that the cultivation system, successfully employed in the homegarden, uses an uncommon edaphic environment. This occurs through a traditional crop adaptation to particular areas of thicker soils (“containers”), known traditionally as “precision agriculture”.